Preservation and modification of cultural values in Vietnamese migrant families in Melbourne - Australia - Trần, Thanh Giang (2021)
In Vietnamese families, the cultural values relating to harmony and solidarity, filial piety and gender hierarchy are considered to be important heritage that are shared across generations. However, migrantion my face challenges in maintaining the cultural values in many Vietnamese migrant families. To date, there has been little research on the operation of these cultural processes。Through in-depth interviews with 20 first-generation Vietnamese migrant parents and 18 second-generation Vietnamese Australian children in Melbourne-Australia，the study explores which Vietnamese cultural values persist in families after migration; how Vietnamese parents share cultural values with their children，and which cultural values the children adopt，retain，and reject in their lives。It has been shown that Vietnamese language，filial piety，gender hierarchy，and harmony have been shared in Vietnamese migrant families。Some aspects of the values have been modified by the first generation parents。Furthermore，the second generation tended to maintain harmony and solidarity，Vietnamese language in families but they downplayed some values related to age and gender hierarchy。The findings indicate that the cultural values that are beneficial and continue to support Vietnamese families in Australia may remain a strong value while others that have not been seen as suitable in the host culture are not maintained across generations